Oxazolomycins produced by Streptomyces glaucus and their cytotoxic activity. Issue 55 (28th October 2021) - Mu, Yu; Jiang, Yi; Qu, Xiaodan; Liu, Bo; Tan, Junfeng; Li, Guiding; Jiang, Mingguo; Li, Liya; Han, Li; Huang, Xueshi
Abstract : Six oxazolomycins (1–6 ) were isolated from the fermentation broth of a soil-borne bacterial strain, Streptomyces glaucus . Abstract : Six oxazolomycins (1–6 ) were isolated from the fermentation broth of a soil-borne bacterial strain, Streptomyces glaucus . The structures of the new compounds, oxazolomycins D–F (1–3 ) and glaucumycins A, B (6a /6b ), were elucidated by detailed spectroscopic data analysis. Oxazolomycins 1, 2, 4, and 5 demonstrated weak or modest cytotoxic activities against four human cancer cell lines, with IC50 values ranging from 10.6 ± 1.7 to 89.5 ± 6.6 μM (or >100 μM). Further study showed that 4 caused S phase cell cycle arrest in SMMC7721 cells through down-regulating the protein expression of cyclin A2, CDK2. Meanwhile, 4 induced apoptosis in SMMC7721 cells through down-regulating the protein levels of Bcl-2, up-regulating the levels of Bax, and activating the cleavage of caspase-3.